FORGETMENOT (FMN) AN ANDROID APPLICATION FOR ALERTING USB USERS - Md Sani, Zamani; Noordin, Aminurrashid; Ab Rahman, Mohd Rahim (2012)

(untitled)
Universal Serial Bus (USB) devices had evolved and had been very important to the computing world nowadays. Globally more than 20 million USB sticks are lost every year mainly for data storage. Other than that, it involves communication devices to the USB such as wireless presenter and mouse or the data storage in thumb drive and external hard disk drive. Losing any of these devices due to the forgotten issue while working publicly in the lab or cyber café could result to cost issue for replacement or risk in exposing high volume of sensitive data to unknown people. Although there are softwares to guarantee the security of the losing data, it is not enough to recover the data or to replace the losing devices. ForgetMeNot (FMN) is an application for Android OS smartphone, using Bluetooth connection, will alarm the user when accidentally leaving the USB devices. It can be used for all the USB devices as long as the USB devices are embedded with the Bluetooth module. With the lower cost of Bluetooth modules, it is an advantage to the USB devices producer, to embed their USB devices with Bluetooth module to give options to user enabling the FMN to avoid missing USB devices.